The Physical and Mechanical Properties of Oil Palm Empty Fruit Bunch Fibre (OPEFB) Based on Various Fibre-Cement Ratios - Zakaria, Mohammad Atif; Nik Soh, Nik Mohd Zaini (Recent Trends in Civil Engineering and Built Environment, 2024)
Empty fruit bunch (EFB) is one of the potential alternative in producing cement boards due to its abundant supply and favourable physicochemical characteristics which benefit in many ways. The focus of this research is to examine natural residues which is empty fruit bunches from palm oil that have been used as reinforcing materials in the manufacture of cement boards that related to various ratio. This experimental research work conducted to explore the role of cement to EFB ratio on the mechanical performances of cement boards. Furthermore, densities of 1200kg / m3 with a cement: EFB 2:1, 2.5:1 and 3:1 ratio were exploited to get the finest performance from this EFBCB. On the other hand, the EFBCB test, which was invented matching to BS standards, containing thickness monitoring (BS EN 3241: 1993), density test (BS EN 323: 1993), elastic modulus (BS EN 310: 1993), modulus of rupture (BS EN 310: 1993), thickness swelling (BS EN 317: 1993) and internal bonding (BS EN 319: 1993). The optimum density for EFB cement panels was discovered to be sample with ratio 3:1 at the end of this project. It displayed the last monitoring readings for thickness was 12.38 mm, highest density 1239 kg / m3, lowest thickness swelling 3.63%, highest internal bonding 0.299 N / mm2, highest MOE and MOR 1105.13 N / mm2 and 3.46 N / mm2. Simply put, the results of this study prove that EFB has a great capacity to be the most advanced material in the country's construction industry.